Medical Imaging 2017: Imaging Informatics for Healthcare, Research, and Applications 2017
DOI: 10.1117/12.2254618
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype analysis of early risk factors from electronic medical records improves image-derived diagnostic classifiers for optic nerve pathology

Abstract: We examine imaging and electronic medical records (EMR) of 588 subjects over five major disease groups that affect optic nerve function. An objective evaluation of the role of imaging and EMR data in diagnosis of these conditions would improve understanding of these diseases and help in early intervention. We developed an automated image-processing pipeline that identifies the orbital structures within the human eyes from computed tomography (CT) scans, calculates structural size, and performs volume measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Two studies in this review focused on the field of glaucoma and used supervised machine learning techniques to improve diagnosis and predict progression. 16 , 22 In the study by Chaganti et al., 16 a good performance was obtained (AUC of glaucoma diagnosis 88%), and results showed that the addition of an EMR phenotype could improve the classification accuracy of a random forest classifier with imaging biomarkers. 16 On the other hand, Baxter et al.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Two studies in this review focused on the field of glaucoma and used supervised machine learning techniques to improve diagnosis and predict progression. 16 , 22 In the study by Chaganti et al., 16 a good performance was obtained (AUC of glaucoma diagnosis 88%), and results showed that the addition of an EMR phenotype could improve the classification accuracy of a random forest classifier with imaging biomarkers. 16 On the other hand, Baxter et al.…”
Section: Resultsmentioning
confidence: 95%
“… 16 , 22 In the study by Chaganti et al., 16 a good performance was obtained (AUC of glaucoma diagnosis 88%), and results showed that the addition of an EMR phenotype could improve the classification accuracy of a random forest classifier with imaging biomarkers. 16 On the other hand, Baxter et al. 22 reported a moderate performance (AUC 67%) in a study that used EHR data alone to predict risk of progression to surgical intervention in patients with open-angle glaucoma.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations